EVALUASI PROGRAM PENGENDALIAN TUBERCULOSIS DI WILAYAH KERJA PUSKESMAS (Studi di Kota Ambon) - Parera, Lodri; Hadisaputro, Suharyo; Lukmono, Djoko Tri Hadi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
The TB control program has been carried out at each publich health centers in Ambon city. But the decrease in the number of new and old cases is not sufficiently accelerated according to the target, there are still high TB cases and there are also differences or disparities in the number of case detection rates between puskesmas and case detection The highest rate is among the puskesmas with the lowest CDR. This study aims to control tuberculosis in the working area of the health center. The type of research used in this research is descriptive analytic research using an observational approach supported by qualitative research. The sample is the program and also the TB laboratory staff at the Ambon City publich health centers, the holder of 44 respondents. Descriptive data analysis with the results described in narrative form then compared the level of case data. The results showed that the case finding program and treatment of TB patients as well as health promotion were carried out by 100% of the respondents. The TB sputum examination program was well implemented by 18 (81.8%) TB laboratory staff respondents. This is related to suspects that do not return the sputum pot. Program TB officers or laboratory workers have multiple jobs, as well as demographic conditions that are far away and difficult to reach by vehicle. Selection of places for TB promotion activities and health centers that are far from where the community lives. Laboratory conditions that should be separate and small for TB. Laboratory staff receive poor quality sputum provided by program holders. The TB control program is carried out and has been running well, but there are several conveniences that the sputum pot cannot return, demographics, treatment at other health facilities, inadequate space and not good enough sputum quality.